Association of Mitochondrial DNA Genomic Variation With Risk of Pick Disease. (30th March 2021) - Valentino, Rebecca R.; Heckman, Michael G.; Johnson, Patrick W.; Baker, Matthew C.; Soto-Beasley, Alexandra I.; Walton, Ronald L.; Koga, Shunsuke; Roemer, Shanu F.; Suh, EunRan; Uitti, Ryan J.; Trojanowski, John Q.; Grossman, Murray; et al.
Abstract : Objective: To determine whether stable polymorphisms that define mitochondrial haplogroups in mitochondrial DNA (mtDNA) are associated with Pick disease risk, we genotyped 52 pathologically confirmed cases of Pick disease and 910 neurologically healthy controls and performed case-control association analysis. Methods: Fifty-two pathologically confirmed cases of Pick disease from Mayo Clinic Florida (n = 38) and the University of Pennsylvania (n = 14) and 910 neurologically healthy controls collected from Mayo Clinic Florida were genotyped for unique mtDNA haplogroup-defining variants. Mitochondrial haplogroups were determined, and in a case-control analysis, associations of mtDNA haplogroups with risk of Pick disease were evaluated with logistic regression models that were adjusted for age and sex. Results: No individual mtDNA haplogroups or superhaplogroups were significantly associated with risk of Pick disease after adjustment for multiple testing ( p < 0.0021, considered significant). However, nominally significant ( p < 0.05) associations toward an increased risk of Pick disease were observed for mtDNA haplogroup W (5.8% cases vs 1.6% controls, odds ratio [OR] 4.78, p = 0.020) and subhaplogroup H4 (5.8% cases vs 1.2% controls, OR 4.82, p = 0.021). Conclusion: Our findings indicate that mtDNA variation is not a disease driver but may influence disease susceptibility. Ongoing genetic assessments in larger cohorts of Pick disease are currently underway.